FAKTOR-FAKTOR YANG MEMENGARUHI INDIVIDU DALAM MENGGUNAKAN PEER TO PEER LENDING DAN EQUITY CROWD FUNDING DI DKI JAKARTA - Ascaryo Putro; Hendratmoko Hendratmoko (Jurnal Manajemen, 2019)
Financial Technology (Fintech) is rife in finance. Fintech giving advantages to users such as efficiency, and also capable to increase financial inclusion in Indonesia. Peer to Peer Lending service, and Equity Crowdfunding are currently becomeing a trend. The research purpose is to find out what factors influencing individuals in using these digital financial services. This research was conducted in DKI Jakarta by collecting 349 respondents consisting of various demographic characteristics and using the Purposive Random Sampling sampling method. The variables used in research are adaptations of the UTAUT (The Unified Theory of Acceptance and Use of Technology) theory. The results obtained in the form of Performance Expectant Variables and Effort Expectancy have a positive and significant effect on Behavioral Intention of Peer to Peer Lending Services, while Social Influence, Trust, Reputation, and Self Efficacy variables have no positive and significant influence on Behavioral Intention of Services Peer to Peer Lending. Then for Equity Crowdfunding Services the results obtained in the form of Performance Expectancy Variables have a positive and significant effect, while the other 5 variables namely Effort Expectancy, Social Influence, Trust, Reputation, and Self Efficacy do not have a positive and significant effect on Behavioral IntentionKey Words : Fintech, UTAUT, Peer to Peer Lending, Equity Crowdfunding, Performance Expectancy, Effort Expectancy, Social Influence, Trust, Reputation, Self Efficacy, Behavioral Intention.